The emergence of an economic technocracy in Colombia, 1948-1974 - Guiot-Isaac, AM (2022)
This dissertation studies the emergence of an economic technocracy in Colombia between 1948 and 1974. It accounts for the advent of professional economists as experts and shows how they succeeded at carving their way into the state to intervene in economic decision-making. Before the mid-twentieth century, men with practical knowledge about public and private finances had generally overseen the administration of economic affairs. In the period under consideration in this dissertation, economics departments and research centres were established in universities, allowing state institutions to incorporate a new type of specialist with a more technically and scientifically grounded expertise about the economy. Based on research in Colombian and US archives as well as interviews, this dissertation explores the resulting professionalisation of economics and institutionalisation of economic expertise in the state. It shows that these processes were embedded in the redemocratisation project of the National Front (1958-1974), following a decade of political turmoil during La Violencia (1948-1957). They were also shaped by the transnational exchanges with foreign actors and institutions that the post-WWII international order made possible for governments in developing countries. Colombia became a favorite client of multilateral institutions and philanthropic foundations, which sponsored several development and technical assistance missions to this country from the late-1940s to the mid-1970s. Hence, the Colombian case provided a privileged lens to analyse more broadly how the transnational circulation of expertise about economic development in the post-WWII period triggered the educational and institutional reforms that entrenched the position of economists in government.